Minor population of NK lymphocytes with CD19 coexpression - A. A. Kalashnikova; N. V. Bychkova (Медицинская иммунология, 2024)
Single reports were published concerning a minor subpopulation of NK cells with weak coexpression of the B cell antigen CD19 in the patients’ blood and bone marrow. The frequency and relative number of CD56+CD19+dim cells is virtually not assessed, and there is no data on their phenotypic characteristics, as well as the connection of this subpopulation with any disease state. The purpose of the present study was to assess the frequency, relative quantity and phenotypic characteristics of CD56+CD19+dim lymphocytes in blood of patients referred for assessment of the lymphocyte subpopulation profile. Peripheral blood of immunocompromised individuals was taken, and subpopulation composition of lymphocytes was determined using eight-color flow cytometry (markers: CD3, CD4, CD8, CD19, CD25, CD45, CD56, HLA-DR). To estimate incidence of the CD56+CD19+dim subpopulation, we have carried out a retrospective analysis of LMD files on 1210 studies for 935 patients (average age, 39.8±14.7 years old) including 84 children under 18 years old. The study was performed repeatedly for some patients. Phenotyping of CD56+CD19+dim cells was performed using a panel of antibodies to B cell, T/NK cell antigens. The occurrence of blood samples containing CD56+CD19+dim was 1.2%, with a relative content of 2.1±1.9% among total lymphocyte population (0.8±0.6% of leukocytes). Long-term persistence of the subpopulation was noted in the patients throughout the entire observation period. The comparison of specific marker expression by NK CD56+CD19+dim, and CD56+CD19- cells revealed high expression of CD2, CD57, reduced expression density of CD7, CD16, CD38. The phenotype of the studied NK cell subpopulation was as follows: CD56+dimCD19+dimCD2+brightCD7+dimCD11c+CD16+dimCD38+dimCD45RA+CD57+CD94+dimNKG2D+CD3-CD4-CD5-CD20-CD21-CD25-CD45R0-CD62L-CD79b-CD117-, with variable expression of CD8 and HLA-DR. The phenotype is consistent with activated terminally differentiated adaptive NK associated with cytomegalovirus infection. The individuals with CD56+CD19+dim had a history of CMV-infection and reactivation of chronic EBV-infection at the time of the study. A probable cause of CD19 coexpression may be trogocytosis of B cell membrane fragments by natural killer cells during active EBV-infection. CD56+CD19+dim lymphocytes can reach noticeable values thus altering the results of studies performed by flow cytometry. The errors are most likely to occur upon assessing the minimal residual disease levels in acute B cell leukemias. The minor CD56+CD19+dimNK subpopulation may be detected in routine immunological analysis. Its functional features and association with certain disorders require further studies.